Prediction of Mechanism and Thermochemical Properties of O3 + H2S Atmospheric Reaction - Morteza Vahedpour; Reza Baghary; Freshte Khalili (Journal of Chemistry)
Ozone and hydrogen sulfide reaction mechanism including a complex was studied at the B3LYP/6-311++G(3df,3pd) and CCSD/6-311++G(3df,3pd)//B3LYP/6-311++G(3df,3pd) levels of computation. The interaction between sulfur atom of hydrogen sulfide and terminal oxygen atom of ozone produces a stable H2S-O3 complex with no barrier. With the decomposition of this complex, four possible product channels have been found. Intrinsic reaction coordinate, topological analyses of atom in molecule, and vibrational frequency calculation have been used to confirm the suggested mechanism. Thermodynamic data at T = 298.15 K and the atmospheric pressure have been calculated. The results show that the production of H2O + SO2 is the main reaction channel with ΔG° = −645.84 kJ/mol. Rate constants of H2S + O3 reaction show two product channels, SO2 + H2O and HSO + HOO, which compete with each other based on the temperature.